Using The Modified Jones Model And Loan Loss Provisions Model (Llps) To Evaluate Earnings Management Practices (Applied Study On Syrian Corporation) - عيسى , ريم; الهندي, طارق (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to detect earnings management practices in banks and companies Syrian contribute to listed and non-listed in the Damascus Securities Exchange, where the study was conducted on a comprehensive sample of 31 companies representing (12) bank and (19) companies belong to different sectors during the period from 2008 to 2012. To measure the phenomenon of earnings management study is based on the optional maturity and applied to estimate the contribution of Syrian companies, except banks using (Modified Jones Model 1995). As has been the use of loan-loss provisioning model (LLPs) to apply to the banks. The results of the study to confirm that most of the companies and banks to contribute to the Syrian listed and unlisted market Damascus Securities exercised earnings management during the period studied (8 banks exercised earnings management of the bank out of 12. 13 Company exercised earnings management company out of 19). It also showed that most of the industrial and service corporations exercised Optional maturity in a negative way, while most of the agricultural contribution and insurance companies companies exercised Optional Merit positive manner, the study showed increased exercise earnings management in 2012 when Syrian contribute to listed and non-listed companies for up to 84%.